Protein fraction, degradability and digestibility of pearl millet silage at different cutting ages - Katia Cylene Guimarães; Kátia Aparecida de Pinho Costa; Alexsandra Paludo; Nayara Fernandes dos Santos; Robson Marcelo Rossi; Welma Santos Cruvinel (Acta Scientiarum. Animal Sciences, 2014)
The determination of protein fraction and rumen fermentation characteristics of pearl millet genotypes is important, since generate information about food nutritional value and also guide the breeding programs of genotypes to be used in diets of ruminants. The objective of this research was to determine the digestion rates of protein fractions, dry matter degradability and in vitro dry matter digestibility of silages from pearl millet genotypes produced at different cutting ages. The experiment was carried out on the Agronomy campus of theRioVerdeUniversityand on the Rio Verde campus of Goiano Federal Institute. The experimental design was randomized blocks with four replications in a 5 x 3 factorial arrangement, with five genotypes of millet: ARD 500, ADR 7010, LAB 0730, LAB 0731 and LAB 0732 and three cutting ages: 57, 65 and 73 days after sowing (DAS). The silage produced from pearl millet, regardless of genotype can be considered of good quality. The evaluated genotypes are considered early, so that the age that provided the best silage quality was 57 DAS. This age provided higher fractions A, lower fraction C and high degradability and digestibility.